Fast DCT-2 transform via Hadamard transform - Armen Petrosyan; Hakob Sarukhanyan (Изд-во НАН РА)
In this paper we present Walsh-Hadamard transform (WHT) based on the fast discrete cosine transform (DCT-2) algorithm. The basic idea of this algorithm is the following: at ¯rst we compute the WHT coe±cients, then using so called conversion matrix we convert these coe±cients to the transform domain coeficients.
Keywords: Mathematics; Algorithm